Sulphur phenomenon in Lake Batur : A Disaster to Local Fisherman - I Gede Mas Suputra (Bali Tourism Board, 2021)
Lake Batur provides a perfect area for fisheries. one of the amazing products from lake Batur is Oreochromis mossambicus, or in the local language called Mujair. The fish has a high economic value for the community. However, in 2009, the villager claimed there was a sudden change in the water quality of Lake Batur. Many anglers often lose their fortune because of the sudden dead fish phenomenon. The lake water was no longer as safe as it used to be for both humans and fish. The local community accused sulphur as the cause of their unfortunate. Several studies have been conducted in Lake Batur every year and indicate several sulphur spots near Buahan Village that appear in January, April, or August. Entering July 2021, around 70 fish in floating net cages owned by farmers in the Lake Batur area died. The case in July 2021 was the worst in history. Research on floating net cells mentioned that the public could predict this mass death event to reduce the fishers’ future losses.